El Principio Socioantrópico: La conexión libertad-determinismo y una nueva estructura explicativa para las ciencias sociales - Jorge Gibert Galassi (Principia: An International Journal of Epistemology)
My purpose is to postulate a principle, which I call “socioantropic”, that can connect in a proper way two historically antithetical notions: free will and determinism in the social word. The main consequence of this is the establishment of a new kind of explanatory structure more in keeping with the special nature of the social sciences. To this end, I shall reconstruct the conventional structure of deductive-nomological explanations, exposing its shortcomings in relation to the social sciences, and hence I shall formulate a proposal for the theoretical resolution of the problem of explanation in the social world.